Unraveling Cajal's view of the olfactory system - Figueres-Oñate, María; Gutiérrez, Yolanda; López-Mascaraque, Laura (Frontiers in Neuroanatomy, 2014)
The olfactory system has a highly regular organization of interconnected synaptic circuits from the periphery. It is therefore an excellent model for understanding general principles about how the brain processes information. Cajal revealed the basic cell types and their interconnections at the end of the XIX century. Since his original descriptions, the observation and analysis of the olfactory system and its components represents a major topic in neuroscience studies, providing important insights into the neural mechanisms. In this review, we will highlight the importance of Cajal contributions and his legacy to the actual knowledge of the olfactory system.